Plant mitochondrial retrograde signaling: post-translational modifications enter the stage - Hartl, Markus; Finkemeier, Iris (Frontiers in Plant Science, 2012)
Beside their central function in respiration plant mitochondria play important roles in diverse processes such as redox homeostasis, provision of precursor molecules for essential biosynthetic pathways, and programmed cell death. These different functions require the organelle to communicate with the rest of the cell by perceiving, transducing and emitting signals. As the vast majority of mitochondrial proteins are encoded in the nuclear genome, changes in mitochondrial status must be fed back to the nucleus to coordinate gene expression accordingly, a process termed retrograde signaling. However, the nature of these signaling pathways in plants and their underlying signaling molecules - or indirect metabolite or redox signals - are not completely resolved. We explore the potential of different post-translational modifications (PTMs) to contribute to mitochondrial retrograde signaling. Remarkably, the substrates used for modifying proteins in many major PTMs are either central metabolites or redox-active compounds, as for example ATP, acetyl-CoA, NAD+, and glutathione. This suggests that the metabolic status of organelles and of the cell in general could be indirectly gauged by the enzymes catalyzing the various PTMs.